2022
DOI: 10.3390/pathogens11121459
|View full text |Cite
|
Sign up to set email alerts
|

Ten Years of African Swine Fever in Ukraine: An Endemic Form of the Disease in the Wild Boar Population as a Threat to Domestic Pig Production

Abstract: (1) Background: African swine fever (ASF) has been present in Ukraine for more than ten years (2012–2022). The purpose of our study was to perform a retrospective analysis of the spread of ASF to assess the role of wild boar in the epizootic expansion in Ukraine. (2) Methods: Statistical materials were collected and the epizootic situation of ASF from 2012 to 2022 was examined. The potential sources of the African swine fever virus (ASFV) and transmission factors were analysed. The main factors exerting negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Whether this trend continues in Ukraine remains to be determined, and it has been suggested that ASF may have become endemic in Ukraine [ 59 ]. In 2021, Ukraine reported only thirteen outbreaks in domestic pigs and three cases of ASF in wild boar [ADNS].…”
Section: Discussionmentioning
confidence: 99%
“…Whether this trend continues in Ukraine remains to be determined, and it has been suggested that ASF may have become endemic in Ukraine [ 59 ]. In 2021, Ukraine reported only thirteen outbreaks in domestic pigs and three cases of ASF in wild boar [ADNS].…”
Section: Discussionmentioning
confidence: 99%
“…З початку повномасштабного вторгнення рух російських військ відбувався з територій Брянської, Курської та Білгородської областей, де неодноразово виявляли ДНК вірус африканської чуми свиней не тільки серед поголів'я свійських та диких тварин, а й у продуктах харчової промисловості. Саме це в сукупності зі зниженням загального рівня біобезпеки господарств через надзвичайну ситуацію у країні становить значну небезпеку щодо розповсюдження не тільки АЧС, а й інших інфекційних хвороб тварин (Omelchenko et al, 2022).…”
Section: вступunclassified
“…the Baltic countries, the Republic of Korea), and others seeing cases mostly among domestic pigs (e.g. Romania, Ukraine, China, and much of southeast Asia) with likely spillover to-and-from wild boar (2)(3)(4)(5)(6)(7). In many countries, spillover is highly suspected but the current surveillance bias is likely to prevent accurate evaluation of this transmission route (6).…”
Section: Introductionmentioning
confidence: 99%